PELATIHAN DAN PERTUNJUKAN DRUMBAND BAGI SISWA SMP NEGERI 30 KABUPATEN MUARO JAMBI DALAM MENINGKATKAN KETERAMPILAN BERMUSIK - Indra Gunawan; Mahdi Bahar; Ikhsan Satria Irianto; Riswani (PT. Jurnal Center Indonesia Publisher, 2025)
The Independent Curriculum in elementary to high schools (SD to SMA) is a challenge for schools to improve their ability in managing both learning and administration, so that what is aspired to in the mandate of the Constitution which reads